The effect of financial allowances on the immigration employees’ performance (Case study: Kilimanjaro region of Tanzania) - Maria Egito; Hezron Onyancha; Adam Chidyau (New Applied Studies in Management, Economics & Accounting)
This study aimed to examine the effect of financial allowances on the immigration employees’ performance (Case study: Kilimanjaro region of Tanzania). The study was guided by Clayton Alderfer's ERG theory of Motivation and used a convergent research design under a mixed research approach. 119 immigration officers from district offices were selected through simple random sampling techniques, while six (6) District Immigration Officers (DIOs and one Regional Immigration Officer (RIO) were selected through a purposive sampling technique from a population of 183 immigration employees. Both content and face validity were utilized to ensure the quality and appropriateness of the chosen instruments. For validity, the researcher consulted the research examiners and supervisor for the review of the research instrument, and they provided feedback on its appropriateness. Reliability of questionnaires for immigration officers, Cronbach's Alpha analysis was run and obtained a coefficient of 0.78, which was acceptable as reliable. Quantitative data were analyzed through the aid of SPSS and contextual analysis, and are present in quotations. From the findings, it was concluded that adequate allowances retain talented employees in the immigration department, also adequate allowances reduce financial stress, allowing employees to focus on their work significantly contributes to immigration employees’ performances in Kilimanjaro Region, Tanzania. Based on the conclusions of this study, it was recommended that the immigration department ensure the provision of suitable allowances to immigration employees to enhance their performance and job satisfaction, which should be granted promptly.